(untitled) (Bangladesh Journal of Zoology, 2026)
Wetlands are among the most productive ecosystems on earth and provide critical habitats for a wide range of avian species. A study on the impact of wetland management on the diversity and habitat utilization pattern of waterbirds was carried out from January 2024 to July 2024 at Jahangirnagar University campus. Bird species were recorded using point count method and fixed-route monitoring. A total of 25 species under 13 families were observed during the study period. Unmanaged lake had the highest diversity of birds (H’= 2.015, D= 0.833) compared to managed (H’= 1.616, D= 0.708) and partially managed wetlands (H’= 1.943, D=0.822). Wetland birds showed a clear preference for edge habitats (44%), followed by tree-adjoining wetlands (32%) and open water (24%). The current assessment of the status of wetland birds revealed 37% were common, 25% very common, 29% rare, and 8% as uncommon. Water parameters such as Dissolved Oxygen (DO) had a weak positive correlation with bird abundance (r= 0.42), while Total Dissolved Solid (TDS) and Temperature showed strong negative correlations (r= –0.81 and r= –0.87, respectively). The infrastructure development, uncontrolled growth of aquatic vegetation, pollution of waterbodies and anthropogenic disturbances such as noise from vehicles and loud human activity were identified as potential threats to wetland birds. Bangladesh J. Zool. 53(3): 323-331, 2025